Implikasi Perkembangan Geopolitik Kawasan Indo-Pasifik Terhadap Keketuaan Indonesia di Asean 2023 - Riqi Samsurizal; Ali Abdullah Wibisono; Abdul Rivai Ras (SENTRI: Jurnal Riset Ilmiah, 2026)
The presence of America and China in the geopolitical competition in the Indo-Pacific region has a significant impact on security and defense stability and carries the potential to trigger open conflict. The growing rivalry between these two major powers influences regional dynamics, particularly in strategic areas such as maritime security, military alliances, and economic influence. As a result, geopolitical escalation in the Indo-Pacific also has important implications for Indonesia’s chairmanship status in ASEAN in 2023. Indonesia, as a central actor in Southeast Asia, faces complex challenges in maintaining regional stability while balancing relations with competing global powers. Therefore, anticipatory efforts are needed from the government to manage geopolitical risks and to promote cooperation that is mutually beneficial for both parties. Indonesia is expected to strengthen diplomatic initiatives, reinforce ASEAN centrality, and encourage dialogue-based conflict management to prevent escalation. This study employs several theoretical frameworks, including constructivism theory and classical geopolitical theories proposed by Fredrick Ratzel, Halford Mackinder, and Alfred Thayer Mahan, to analyze the interaction between power, geography, and regional politics. Data collection in this study uses secondary data, which is analyzed through document analysis and supported by data triangulation to ensure validity. The results show that geopolitical escalation has a significant impact on Indonesia’s chairmanship status in ASEAN, particularly in shaping its diplomatic strategies, leadership role, and efforts to maintain regional peace and cooperation.